Sociolinguistics and deaf communities - Lucas, Ceil (Cambridge University Press, 2015)
An up-to-date overview of the main areas of the sociolinguistics of sign languages. Topics explored include multilingualism in the global deaf community, sociolinguistic variation and change in sign languages, bilingualism and language contact between signed and spoken languages, attitudes towards sign languages, and sign language planning and policy.